Predicting transformations during reactive flash sintering in CuO and Mn2O3. Issue 1 (11th September 2020) - Murray, Shannon E.; Lin, Yu‐Ying; Sulekar, Soumitra S.; Gebre, Mebatsion S.; Perry, Nicola H.; Shoemaker, Daniel P.
Abstract: Reactive flash sintering has been demonstrated as a method to rapidly densify and synthesize ceramic materials, but determining the extent of chemical reactions can be complex since the maximum temperature reached by the sample may be brief in time. The black body radiation (BBR) model has been shown to accurately predict the sample temperature during the steady state of flash (stage III). This work demonstrates situations where the BBR model alone does not accurately predict when a phase transformation will occur. We examine the model reactions of CuO reduction to Cu2 O during stage II and Mn2 O3 reduction to Mn3 O4 in stage III. In CuO, highly resistive samples result in initially localized current flow, a stochastic process resulting in inhomogeneous heating and error in the BBR model during stage II. CuO reduction does not occur in constant heating rate experiments with 6.25 V/mm fields, even though the sample temperature momentarily exceeds the phase transformation temperature. Increased furnace heating to 950°C before application of a field is required to drive the transition. In Mn2 O3, the calculated sample temperature of the gauge is less than the transformation temperature, but localized heating at the contact will exceed the transformation temperature, causing the transformation to propagate away from the electrode during stage III. This work demonstrates two forms of inhomogeneity (local, stochastic current flow, and local contact resistance) that result in a complex thermal profile of the sample. This profile should be interrogated to understand reaction kinetics, and can be beneficial when engineered.